Pentacarbonyl-1κ(2) C,2κ(3) C-(μ-pyrazine-2,3-dithiolato-1:2κ(4) S,S′:S,S′)(trimethylphosphane-1κP)diiron(I)(Fe—Fe) - Gao, Shang (International Union of Crystallography, 2011)
In the title compound, [Fe(2)(C(4)H(2)N(2)S(2))(C(3)H(9)P)(CO)(5)], the Fe(2)S(2) core adopts a butterfly conformation. The PMe(3) ligand is coordinated in the basal position, roughly cis to the Fe—Fe bond. The Fe—Fe distance of 2.4970 (6) Å is relatively short compared to those (ca 2.53 Å) found in another monosubstituted diiron compound. A rigid planar dithiolate bridge is featured, with an angle of 2.78 (1)° between the Fe—Fe bond and the normal to the pyrazine-2,3-dithiolate plane.